Identification of the angiogenic gene signature induced by EGF and hypoxia in colorectal cancer. - Khong, T; Thairu, N; Larsen, H; Dawson, P; Kiriakidis, S; Paleolog, E (BioMed Central, 2013)
BACKGROUND: Colorectal cancer (CRC) is characterised by hypoxia, which activates gene transcription through hypoxia-inducible factors (HIF), as well as by expression of epidermal growth factor (EGF) and EGF receptors, targeting of which has been demonstrated to provide therapeutic benefit in CRC. Although EGF has been demonstrated to induce expression of angiogenic mediators, potential interactions in CRC between EGF-mediated signalling and the hypoxia/HIF pathway remain uncharacterised. METHODS: PCR-based profiling was applied to identify angiogenic genes in Caco-2 CRC cells regulated by hypoxia, the hypoxia mimetic dimethyloxallylglycine (DMOG) and/or EGF. Western blotting was used to determine the role of HIF-1alpha, HIF-2alpha and MAPK cell signalling in mediating the angiogenic responses. RESULTS: We identified a total of 9 angiogenic genes, including angiopoietin-like (ANGPTL) 4, ephrin (EFNA) 3, transforming growth factor (TGF) β1 and vascular endothelial growth factor (VEGF), to be upregulated in a HIF dependent manner in Caco-2 CRC cells in response to both hypoxia and the hypoxia mimetic dimethyloxallylglycine (DMOG). Stimulation with EGF resulted in EGFR tyrosine autophosphorylation, activation of p42/p44 MAP kinases and stabilisation of HIF-1α and HIF-2α proteins. However, expression of 84 angiogenic genes remained unchanged in response to EGF alone. Crucially, addition of DMOG in combination with EGF significantly increased expression of a further 11 genes (in addition to the 9 genes upregulated in response to either DMOG alone or hypoxia alone). These additional genes included chemokines (CCL-11/eotaxin-1 and interleukin-8), collagen type IV α3 chain, integrin β3 chain, TGFα and VEGF receptor KDR. CONCLUSION: These findings suggest that although EGFR phosphorylation activates the MAP kinase signalling and promotes HIF stabilisation in CRC, this alone is not sufficient to induce angiogenic gene expression. In contrast, HIF activation downstream of hypoxia/DMOG drives expression of genes such as ANGPTL4, EFNA3, TGFβ1 and VEGF. Finally, HIF activation synergises with EGF-mediated signalling to additionally induce a unique sub-group of candidate angiogenic genes. Our data highlight the complex interrelationship between tumour hypoxia, EGF and angiogenesis in the pathogenesis of CRC.